Physical interpretation of magnetic behavior in nickel zinc ferrite based on dielectric study - Wan Ab Rahman, Wan Norailiana (2012)
Nickel Zinc Ferrite is a soft magnetic material and the properties of ferrite are Nickel Zinc Ferrite is a soft magnetic material and the properties of ferrite are dependent on several factors including the sintering temperature, method of preparation and microstructure. In this research, NixZn1-xFe2O4 with x=0.5 and 0.3 were preapared via the conventional ceramic precessing method. The microstructure,magnetic and dielectric properties were studied to understand the physical, magnetic and dielectric properties of the resulting materials. The X-Ray diffraction results confirm the formation of crystalline samples after sintering at 1260°C, 1300°C and 1340°C for both compositions. The microstructure studies of Ni0.5Zn0.5Fe2O4 and Ni0.3Zn0.7Fe2O4 showed that the grain size increased and the porosity decreased with increasing sintering temperature. The density of the sample also increased with sintering temperature for both compositions. Physical characteristic of samples were studied using X-Ray Diffraction, SEM and TEM. The permeability components μ’,μ’’ and dielectric components ε’, ε dependent on several factors including the sintering temperature, method of preparation and microstructure. In this research, NixZn1-xFe2O4 with x=0.5 and 0.3 were preapared via the conventional ceramic precessing method. The microstructure,magnetic and dielectric properties were studied to understand the physical, magnetic and dielectric properties of the resulting materials. The X-Ray diffraction results confirm the formation of crystalline samples after sintering at 1260°C, 1300°C and 1340°C for both compositions. The microstructure studies of Ni0.5Zn0.5Fe2O4 and Ni0.3Zn0.7Fe2O4 showed that the grain size increased and the porosity decreased with increasing sintering temperature. The density of the sample also increased with sintering temperature for both compositions. Physical characteristic of samples were studied using X-Ray Diffraction, SEM and TEM. The permeability components μ’, μ’’ and dielectric components ε’, ε’’ were measured using Impedance Analyzer. The permeability and permittivity for both compostions were observed to increase with increasing sintering temperature due to the contribution of the increasing grain size. Also they decreased with increasing frequency for both compositions. It was also observed that the sample with composition Ni0.3Zn0.7Fe2O4 has higher permeability and permittivity than Ni0.5Zn0.5Fe2O4. From the permittivity and permeability data, dielectric complex-plane plot and magnetic complex-plane plot were obtained.The plots revealed the mechanism of polarization. The dielectric polarization was contributed by the interfacial and dipolar polarizations. Meanwhile the magnetization process were probably dominated by magnetic domain wall movement and magnetic spin rotation. Each polarization and magnetization process was dominant in a particular frequency range. The variation of the real part of permeability with temperature was measured for both composition at a constant frequency, 10 kHz. For samples with composition, Ni0.5Zn0.5Fe2O4 the temperature range is from room temperature to 250°C and for samples with composition Ni0.3Zn0.7Fe2O4 the temperature range is from room temperature to 100°C. The Curie temperature where the ordered state magnetic moment almost totally disappears was observed for Ni0.5Zn0.5Fe2O4 to be 250°C and for Ni0.5Zn0. 5Fe2O4 to be 100°C.